Hemoglobin Levels on Trichuris trichiura Infection in Children - Ni Putu Aryadnyani; Dewi Inderiati; Fauzia Ulfah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Worm infections often caused by worms transmitted through the soil (Soil-Transmitted Helminths). Types of STH worms include roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura) and hookworms (Ancylostoma duodenale and Necator Americanus). Worms commonly suffered by school-age children with the most aged between 5-14 years. Worms can affect the intake, digestion, absorption, and metabolism of food, which can result in loss of protein, carbohydrates, fats, and vitamins. Trichuris trichiura and hookworm can cause massive amounts of blood loss and decreased hemoglobin levels. This study aims to determine the relationship of Trichuris trichiura infection with hemoglobin levels in children in the village of East Serang Kilasah, Banten. This research is an analytic survey with a cross-sectional design with 42 respondents. The sampling technique used was purposive sampling. The results of the fecal examination by the Kato-Katz method found 23 children (54.76%) with mild worm levels and 19 children (45.24%) with moderate worm levels. The results of blood tests found 36 children (85.71%) with normal hemoglobin levels and six children (14.79%) with low hemoglobin levels. Based on the results of statistical tests, the results obtained P-value 0.004 (P-value